Inferior Alveolar Nerve Impairment Subsequent To Reduction Of Mandibular Fractures - Nighat Zahid; Aqib Sohail; Aneela Amjad; Shahid Adil Khalid (ziauddin University, 2022)
Background: Consequent Injury to branches of the trigeminal nerve is a well-recognized risk of dental and oral surgical procedures. Neurosensory impairment of inferior alveolar nerve is seen in traumatic mandibular fractures and after the reduction of these fractures. We conducted a study at Oral & Maxillofacial Surgery Department of Lahore Medical and Dental College from November 2016 to July 2017, to assess the frequency of inferior alveolar nerve impairment after reduction of open and close mandibular fractures. Methods: In this randomized controlled trial 60 patients with mandibular fractures between lingula and symphysis and matching the inclusion criteria were inducted and allocated into two groups; Group 1 patients were treated by open reduction and internal fixation by 2mm mini hole plate. Group 2 were treated by closed reduction achieved by eyelet intermaxillary fixation. The inferior alveolar nerve function was clinically evaluated on seventh postoperative day. The results of these evaluations were recorded in a specially designed proforma. Data was analyzed by using SPSS Version 10.0. Results: The mean age of patients was 25.25 ± 9.207 years (range 15 to 60). In this study there were 53 (88.3%) males and 7 (11.7%) females (male to female ratio 7.57: 1). Using chi-square test we found closed reduction group was statistically significant [p-value = 0.001 (< 0.0001)]. in getting the higher NST score compared to open reduction. Conclusion: There is relatively greater risk of sensory impairment of inferior alveolar nerve with open reduction and internal fixation compared to closed reduction of mandibular fractures.